Effect of Aluminium Foil Packaging Thickness on the Product Quality of Banana Chips - Oktaviandi, Audri; Purwayantie, Sulvi; Hartanti, Lucky (Universitas Tanjungpura, 2024)
This study aims to analyse the effect of aluminium foil packaging variation on the quality of kepok banana chips based on the parameters of moisture content, ash content, free fatty acid, colour, texture, and organoleptic test. The two types of packaging used were Full Aluminium Foil (0.3 mm) and Plastic Combination Aluminium Foil (0.2 mm), with a product shelf life of 30 days. Quality parameters were tested using moisture content, ash content, free fatty acids and sensory analysis, including colour and texture. The results showed that the packaging variation had no significant effect on moisture content, ash content, colour, and texture, but had a significant effect on free fatty acid content. The kepok banana chips produced did not meet the standard of fruit chips, both in terms of moisture content, ash content, and free fatty acids. However, the assessment by semi-trained panelists showed preference for the kepok banana chips based on colour and texture.